Variation of Coral Fish Communities in Coral Transplantation Sites, Kecinan Beach, Malaka Village, North Lombok - Ridwan Ridwan; Nurliah Nurliah; Edwin Jefri (Jurnal Biologi Tropis, 2023)
Coral reefs are a very complex ecosystem with a fairly high diversity of biota, the existence of coral fish will be greatly affected by the condition of coral reefs, coral transplantation is an effort to restore coral reefs which aims to improve coral reef ecosystems. This study aims to look at the reef fish community in coral transplant media.  Data collection was carried out on January 15 – February 26, 2023. The method used in this study was a survey method. Data was collected using the Underwater Visual Census (UVC) technique and underwater cameras using SCUBA equipment. Data collection was carried out 4 times by looking at diversity, abundance, and categories based on how they eat. The results of this study obtained 6 families belonging to 13 genera and 15 species of reef fish with a total of 549 individuals. The categories of fish found consisted of 4 categories, namely 3 species of carnivores, 2 species of herbivores, 8 species of omnivores, and 2 species of corallivores. The diversity index value (H') was 1.662, the uniformity index (E) was 0.613, and the dominance index value (C) was 0.266.